Minimasi Slack Time pada Penjadwalan Make To Order Job Shop - Ali Parkhan; Hermawan Adi Tanjung (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2005)
In manufacturing Make to Order environment, order usually can be negotiated in order to satisfycustomer need while it remains considering resources availability. Scheduling is utilized in a company to get higher efficiencies in production, minimize makespan and meet due date. There are some decisions related in scheduling activity i.e. sequencing, routing and determining starting time and finishing time of jobs. This paper will present application of Integer Linear Programming (ILP) and Critical Path Method (CPM) in scheduling. The methods are employed to determine due date that minimize slack time. This study resulted an optimal sequencing and routing of the jobs.